2022
DOI: 10.1007/s12008-022-01023-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibration and noise analysis of acetoxime modified TiO2 coating over steel alloy

Abstract: In this research work, conventional gun spray method is used to coat oximemodi edtitanium(IV) isopropoxide on steel to nd out damping behaviour of coating. The most conventional method is modal analysis is used to measure vibration and noise damping of bare and titania coated samples. Test results revealed that a thin coating has improved the vibration and noise damping when compare with bare sample. SEM, EDX and AFM analysis were carried out to study morphology, coating thickness and composition of coating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Also it can be observed that the overall volume of waste produced by hotels can vary significantly based on factors such as occupancy rates, seasonal fluctuations, and the scale of hotel operations. In the recent time, plastic bags or buckets are commonly used to contain smaller waste items, facilitating ease of collection and disposal [27].…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Also it can be observed that the overall volume of waste produced by hotels can vary significantly based on factors such as occupancy rates, seasonal fluctuations, and the scale of hotel operations. In the recent time, plastic bags or buckets are commonly used to contain smaller waste items, facilitating ease of collection and disposal [27].…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Thermal spray coatings performs crucially in protecting slurry pumps from erosion and corrosion wear [6, 9,[18][19][20][21][22][23][24][25][26][27][10][11][12][13][14][15][16][17]. High-Velocity Oxy-Fuel (HVOF) coatings are thermal spray coatings that provide a dense and hard surface to save the steels and alloys from the abrasive nature of slurry uids.…”
Section: Introductionmentioning
confidence: 99%